2016
DOI: 10.33396/1728-0869-2016-12-3-10
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Aspects of Pollinosis. Literature Review

Abstract: The review is dedicated to the analysis of ecological aspects of pollen allergy (pollinosis). The characteristic of pollen as a natural aerosol component is given. The information related to aeropalinological monitoring and its importance in public health service is presented. The peculiarity of this pathology is its regional variety associated with differences in plant species compositions and pollen periods. The problem of immune response formation to pollen has been studied most profoundly. At that it is kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…It was found that about 100 plant species are important sources of pollinosis, whose role has been confirmed by allergological studies. It is noted that high prevalence of pollinosis is observed in the North Caucasus, Volga and Ural regions of Russia (up to 80% of all patients with allergic rhinitis) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that about 100 plant species are important sources of pollinosis, whose role has been confirmed by allergological studies. It is noted that high prevalence of pollinosis is observed in the North Caucasus, Volga and Ural regions of Russia (up to 80% of all patients with allergic rhinitis) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Загрязнение воздуха, повреждая барьерные функции слизистых оболочек, облегчает проникновение аллергенов и активацию иммунных механизмов. Важную роль играет также микробиом окружающей среды, формируя иммунную систему в раннем детстве и воздействуя на дальнейшее развитие аллергических реакций [43,44].…”
unclassified